Mengembangkan Nilai-Nilai Multicultural dalam Strategi Pembelajaran Aktif di SD Negeri 03 Pekuncen - Sabarhati, Susi; Ningsih, Tutuk (Universitas Pahlawan Tuanku Tambusai, 2025)
Multicultural education is education that covers all students regardless of their groups, such as gender, ethnicity, race, culture, social strata, and religion The role of education is very crucial in instilling mutual respect, respect, and cooperation in diversity. Schools must teach about tolerance which is an appreciation and respect for diversity (plurality) that prioritizes humanism and ethics as the main pillar of the formation of an open society and able to work together in pluralism. Active learning strategies are an approach that is able to increase student involvement in the learning process and encourage them to think critically and work together with classmates who have different backgrounds. The method used in this study is a qualitative method with case studies. Based on observations and interviews with teachers and students, the implementation of multicultural-based active learning strategies in grade 5 of SD Negeri 03 Pekuncen showed several positive impacts, including: 1) Students showed a better understanding of the importance of respecting differences in daily life 2) Discussion-based learning and group work helped students develop communication and cooperation skills 3) With more interactive methods, students are more enthusiastic in participating in lessons 4) Learning that links social and economic diversity with daily life makes it easier for students to understand the materialCooperative learning strategies, thematic discussions, role playing, and project-based learning have increased students' social participation and interaction. Students become more confident, able to work together, and have better communication skills. The diversity of students' socioeconomic backgrounds is not an obstacle to learning, but rather a strength to build understanding and tolerance attitudes. Students learn from each other's experiences and understand that each individual has an important role to play in social life. Keywords: Multicultural, Active Learning Strategies